2003
DOI: 10.1161/01.str.0000074032.64049.47
|View full text |Cite|
|
Sign up to set email alerts
|

Upregulation of CD40-CD40 Ligand (CD154) in Patients With Acute Cerebral Ischemia

Abstract: Patients with acute cerebral ischemia show upregulation of the CD40 system, which might contribute to the known proinflammatory, proatherogenic, and prothrombotic milieu found in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
111
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(123 citation statements)
references
References 32 publications
9
111
1
2
Order By: Relevance
“…Circulating levels of soluble CD40 ligand (sCD40L) are upregulated in systemic vascular diseases, such as ischemic heart disease, stroke, pulmonary hypertension, and even in cigarette smokers (12,16,19,20). Furthermore, we found that CD40 stimulation induces emphysematous change in mouse lung.…”
Section: Sensitization Of Fas-mediated Cell Death By Cd40 And/or Ifn-mentioning
confidence: 85%
“…Circulating levels of soluble CD40 ligand (sCD40L) are upregulated in systemic vascular diseases, such as ischemic heart disease, stroke, pulmonary hypertension, and even in cigarette smokers (12,16,19,20). Furthermore, we found that CD40 stimulation induces emphysematous change in mouse lung.…”
Section: Sensitization Of Fas-mediated Cell Death By Cd40 And/or Ifn-mentioning
confidence: 85%
“…Recent studies demonstrated that sCD40L is enhanced in patients at risk of CVD and in those with acute coronary syndrome suggesting that it may represent a new marker of atherosclerotic progression [16][17][18][19][20]. The behaviour of sCD40L has never been explored in patients with metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of CD40 ligand (CD40L; CD154), a key immune and inflammatory mediator, has emerged as an important contributor to inflammation and atherosclerosis. [1][2][3][4][5][6][7][8] Clinically, elevated levels of circulating soluble CD40L (sCD40L) have been associated with hypercholesterolemia, diabetes, ischemic stroke and acute coronary syndromes, and predict increased restenosis after percutaneous coronary (and carotid) intervention (PCI). 8 -12 Whereas the role of CD40L in experimental atherosclerosis has been examined extensively, relatively little is known about the contribution of elevated CD40L to neointima formation and restenosis, particularly in an atherogenic environment.…”
mentioning
confidence: 99%